Social Science Sequestered - Markusson, Nils; Balta-Ozkan, Nazmiye; Chilvers, Jason; Healey, Peter; Reiner, David; McLaren, Duncan (Frontiers in Climate, 2020)
Greenhouse gas removal (GGR) raises many cultural, ethical, legal, social and political issues, yet in the growing area of GGR research, humanities and social sciences (HASS) research is often marginalised, constrained and depoliticised. This global dynamic is illustrated by an analysis of the UK GGR research programme. This dynamic matters for the knowledge produced and for its users. Without HASS contributions, too narrow a range of perspectives, futures and issues will be considered, undermining or overpromising the prospects for the responsible development of GGR (and threatening worse side-effects), and limiting our understanding of why and how policy demands GGR solutions in the first place. In response, we present policy principles for bringing HASS fully into GGR research, organised around three themes: 1) HASS-led GGR research, 2) Opening up GGR futures, and 3) The politics of GGR futures.